Demoralization narrative: Foul language of community figures - Munjiah, Ma’rifatul (IAS Journal of Localities, 2023)
This study in addition to describing the speech-language in the communication process of community figures will also explain what the meaning behind the speech is. This study is descriptive and qualitative by using the netnography method. Data collection in this study was carried out through a reading process on 500 YouTube videos, using the search keywords "sexual harassment" and "sexual violence". The data in this study are in the form of classifications of speech used by community leaders in the form of text excerpts. This study shows that the speech used by community figures in the communication process does not contain a few dictions that are sexual harassment in verbal and non-verbal forms, such as written, spoken, gesture, touch, and symbolically. The speech used also contains critical and evaluative meanings that reflect the morality of a community figure in the communication process.